Endodontic Outcome of Root Canal Treatment Using Different Obturation Techniques: A Clinical Study - Alexander Winkler; Philipp Adler; Julia Ludwig; Norbert Hofmann; Sebastian Soliman; Gabriel Krastl; Ralf Krug (MDPI AG, 2023)
Objective: To evaluate the clinical outcome of root canal treatment by obturation technique, root canal filling quality, and tooth- and patient-related variables. Methods: This clinical study investigated the endodontic outcome of 114 teeth treated between the years 2009 and 2012. Three different obturation methods were used: (1) adhesive obturation using the continuous wave of condensation technique with Resilon® (CWR), (2) matching-taper single-cone technique with gutta-percha and AH Plus® (SCGP), and (3) matching-taper single-cone technique with gutta-percha and GuttaFlow® (SCGF). Pre- and postoperative periapical radiographs were performed to detect the presence of endodontic lesions (PAI classification) and to assess the quality of both the obturation and the restoration. Tooth- and patient-related data were collected. Results: The overall endodontic success rate was 75.4% after a mean observation period of 6.3 years. There were no significant correlations between the type or overall quality of obturation and the treatment outcome. Teeth with preoperative lesions had the highest odds ratio (factor of 4.98) for endodontic failure. Tooth- and patient-related variables had no significant effect on endodontic outcome. Conclusions: The preoperative periapical status of teeth requiring endodontic treatment was a substantial prognostic factor for endodontic outcome, whereas the type of obturation material or technique did not affect it.